Relationship between Farmers Knowledge Level and Technologies Implementation in Tidal Swamp Land in South Sumatra - Budi Raharjo; Herwenita Herwenita (Sriwijaya Journal of Environment, 2019)
Mechanization and recent technology use in tidal swamp land is encouraged in order to increase farming efficiency and effectiveness. However, a lot of farmers still have less knowledge of new technologies thus field meeting is held as one of ways to accelerate information spread as well as to obtain feedback from farmers shortly. The study aims to determine the relationship between farmers’ level of knowledge and technology implementation by farmers; and farmers’ response on recent technologies introduced. It used a purposive sampling method with 100 participants of field meeting as respondents. Data was retrieved using questionnaires and analyzed descriptively to determine the level of knowledge and technology implementation by farmers while non-parametric Coefficient of Contingency test is used to know its relationship. The study revealed there is no significant relationship between farmers’ level of knowledge and technology implementation. However, farmers responded well and interested in implementing recent technologies in the future hence technology dissemination through field meetings and other dissemination channels should carried out continuously.